Analisis Penerapan Model Pembelajaran Treffinger pada Pembelajaran Matematika di Kelas V SDN Tengki 02 Kabupaten Brebes - Melida Rosiyana; Laelia Nurpratiwiningsih; Yasin Yasin (Journal on Education, 2023)
The purpose of this study was to determine the application of the treffinger learning model in mathematics learning and the teacher's difficulty factor in applying the treffinger learning model to mathematics learning in class V SDN Tengki 02 Brebes Regency. This research method uses qualitative research which was carried out at SDN Tengki 02, Brebes Regency. This research technique uses interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the application of the treffinger learning model is very effective in learning mathematics in improving the creative thinking skills of students who are able to solve given problems, express opinions and express ideas in creative thinking. Teacher difficulty factors that occur in implementing the Treffinger learning model are teacher skills, material preparation, class management, learning time, evaluation and feedback. The learning outcomes obtained before the learning model was applied were 30% of students who scored below the KKM with a value of 65. Using the Treffinger learning model made students more active in learning activities and created a pleasant atmosphere. The Treffinger learning model can be applied in higher classes in mathematics learning.